Construction of strong mammalian promoters by random cis-acting element elongation. (May 2007) - Ogawa, Ryohei; Kagiya, Go; Kodaki, Tsutom; Fukuda, Shigekazu; Yamamoto, Kazutaka
Synthetic oligonucleotides containing one of four kinds of cis-acting elements, binding sites for activating protein-1 (AP-1), nuclear factor κB (NF-κB), CArG binding factor A (CBF-A), and nuclear factor Y (NF-Y), were randomly ligated to construct DNA fragments. These fragments were inserted into the SalI site of a promoter probe vector, pGL3-TATASal, which is located immediately upstream of the TATA box sequence of the human heme oxygenase 1 gene and linked to the luciferase gene to construct 11 plasmid vectors. When these vectors were introduced into PC-3 cells of human prostate cancer, 6 out of the 11 transfectants showed a significantly higher luciferase activity than pGL3-TATASal. The two strongest promoters (clone 6 and clone 11) were investigated further. Clone 6 turned out to be the strongest, showing a 3.0-and 8.4-fold activity in comparison to the two frequently used promoters—the cytomegalovirus (CMV) immediate early promoter and the simian virus 40 (SV40) early promoter, respectively. Clone 11 was less active than clone 6, but still showed higher activity than the two promoters. When the plasmids were introduced into nine other cell lines, their activities varied but were still comparable to the two promoters. These results indicate that the method used here is simple and efficient for constructing strong promoters that are potentially useful for vectors in either gene therapy or recombinant vaccine.